The Influence of Work Environment, Occupational Health and Safety on Employee Performance at PT IHC Orchid Griya Nutrisi - Rahmawati, Aulia; Fauzobihi, Fauzobihi; Irawan, Pristanto Ria (Business Management, 2025)
This study aims to determine the influence of the work environment, occupational health and safety (K3) on employee performance at PT IHC Orchid Griya Nutrisi, North Jakarta. The research approach used was quantitative with a survey method, where data were collected through distributing questionnaires to 60 employees as respondents. Data analysis was conducted using multiple linear regression, with partial tests (t-tests) as the basis for decision-making. The partial test results show that the occupational safety variable has no significant effect on employee performance, as well as the occupational health and work environment variables which have no significant effect on performance. The significance value of occupational safety is 0.889, occupational health 0.548, and work environment 0.746, all greater than the significance limit of 0.05. Simultaneously, the occupational safety (X1), occupational health (X2) and work environment (X3) variables on employee performance (Y) do not have a significant effect. Thus, it can be concluded that partially the work environment, occupational health, and occupational safety do not contribute significantly to improving employee performance at PT IHC Orchid Griya Nutrisi North Jakarta.